Comparison of ixekizumab with ustekinumab in moderate‐to‐severe psoriasis: 24‐week results from IXORA‐S, a phase III study. (1st October 2017) - Reich, K.; Pinter, A.; Lacour, J.P.; Ferrandiz, C.; Micali, G.; French, L.E.; Lomaga, M.; Dutronc, Y.; Henneges, C.; Wilhelm, S.; Hartz, S.; Paul, C.; et al.
Summary: Background: It has been shown that the interleukin (IL)‐23/IL‐17 axis is critical in the pathogenesis of psoriasis. Objectives: To present the primary end point (week 12) and safety and efficacy data up to week 24 from a head‐to‐head trial (IXORA‐S) of the IL‐17A inhibitor ixekizumab (IXE) vs. the IL‐12/23 inhibitor ustekinumab (UST). Methods: Randomized patients received IXE (160‐mg starting dose, then 80 mg every 2 weeks for 12 weeks, then 80 mg every 4 weeks, n = 136) or UST (45 mg or 90 mg weight‐based dosing per label, n = 166). The primary end point was the proportion of patients reaching ≥ 90% Psoriasis Area and Severity Index improvement (PASI 90). Hommel‐adjusted key secondary end points at week 12 included PASI 75, PASI 100, static Physician's Global Assessment (sPGA) score of 0 or 1, sPGA score of 0, Dermatology Life Quality Index (DLQI) score of 0 or 1, ≥ 4‐point reduction on the itch numerical rating scale (NRS) and changes in itch NRS and skin pain visual analogue scale. Results: At week 12, IXE ( n = 99, 72·8%) was superior to UST ( n = 70, 42·2%) in PASI 90 response (response difference 32·1%, 97·5% confidence interval 19·8−44·5%, P < 0·001). Response rates for PASI 75, PASI 100 and sPGA (0, 1) were significantly higher for IXE than for UST (adjusted P < 0·05). At week 24, IXE‐treated patients had significantly higher response rates than UST‐treated patients for PASI, sPGA and DLQI (unadjusted P < 0·05). No deaths were reported, and the treatments did not differ with regard to overall incidences of adverse events ( P = 0·299). Conclusions: The superior efficacy of IXE demonstrated at week 12 persisted up to week 24. The safety profiles were consistent with those previously reported for both treatments.